2017
DOI: 10.1172/jci.insight.90772
|View full text |Cite
|
Sign up to set email alerts
|

Th17 cells are refractory to senescence and retain robust antitumor activity after long-term ex vivo expansion

Abstract: Adoptive immunotherapy for solid tumors relies on infusing large numbers of T cells to mediate successful antitumor responses in patients. While long-term rapid-expansion protocols (REPs) produce sufficient numbers of CD8 T cells for treatment, they also cause decline in the cell's therapeutic fitness. In contrast, we discovered that IL-17-producing CD4 T cells (Th17 cells) do not require REPs to expand 5,000-fold over 3 weeks. Also, unlike Th1 cells, Th17 cells do not exhibit hallmarks of senescence or apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 56 publications
4
72
0
Order By: Relevance
“…41,43 Of interest, two recent papers have demonstrated a role for IL-10 as an unexpected proliferative trigger of infected CD4+ T-cell clones and, possibly, leukemogenesis. 44,45 Corroborating these findings, IL10 was found to be a significant (r = 0.36, p = 0.013) member of the proliferative gene module, together with PCNA and MKI67, in our WGCNA analysis. In addition, RNAseq analysis of purified cells with a CD4 + CCR4 + CD26-CD7-leukemic phenotype from an independent UK cohort revealed IL17C is expressed in "ATL-like" cells.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…41,43 Of interest, two recent papers have demonstrated a role for IL-10 as an unexpected proliferative trigger of infected CD4+ T-cell clones and, possibly, leukemogenesis. 44,45 Corroborating these findings, IL10 was found to be a significant (r = 0.36, p = 0.013) member of the proliferative gene module, together with PCNA and MKI67, in our WGCNA analysis. In addition, RNAseq analysis of purified cells with a CD4 + CCR4 + CD26-CD7-leukemic phenotype from an independent UK cohort revealed IL17C is expressed in "ATL-like" cells.…”
Section: Discussionsupporting
confidence: 69%
“…Defects in the Th17 axis increase vulnerability to S. aureus and Candida albicans infections, whereas in vivo S. aureus primed memory Th17 cells inhibited IL‐17 production and increased IL‐10 production . Of interest, two recent papers have demonstrated a role for IL‐10 as an unexpected proliferative trigger of infected CD4+ T‐cell clones and, possibly, leukemogenesis . Corroborating these findings, IL10 was found to be a significant ( r = 0.36, p = 0.013) member of the proliferative gene module, together with PCNA and MKI67 , in our WGCNA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This situation can be further exacerbated by conventional ex vivo cell manufacturing processes (19,20,57,58). We therefore next asked whether AKTi preserves key markers of cellular differentiation and effector function relative to an unstimulated starting population of T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, relatively differentiated T cell products are generated using many current clinical manufacturing methods for genetically engineered T cells because these methods focus primarily on the generation of large numbers of antitumor cells (19,20). This is especially true in heavily pretreated patients who have starting apheresis populations containing a paucity of naive/ early memory T cells (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, many studies have indicated that a T H 1 phenotype is preferable for ACT; however, recent work indicates that T H 17 polarized CD4 + T cells are able to exert superior antitumor immunity over T H 1 cells by resisting apoptosis and senescence 106 . Importantly, tumor destruction still depends on the T H 1 cytokine IFNγ and CD8 + T cells.…”
Section: Help In Therapeutic Contextmentioning
confidence: 99%